2016
DOI: 10.1016/j.jana.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Fellowship Training for Emerging Global Health Leaders in Africa to Improve HIV Prevention and Care: The Afya Bora Consortium

Abstract: HIV continues to challenge health systems, especially in low- and middle-income countries in Sub-Saharan Africa. A qualified workforce of transformational leaders is required to strengthen health systems and introduce policy reforms to address the barriers to HIV testing, treatment, and other HIV services. The 1-year Afya Bora Consortium Fellowship in Global Health capitalizes on academic partnerships between African and U.S. universities to provide interprofessional leadership training through classroom, onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The well-funded medical project related to HIV prevention and care (8) and the longstanding nursing leadership programs (9) concentrated mostly on leadership along with active learning projects. The LI is the first project to our knowledge focusing on rehabilitation leaders.…”
Section: Discussionmentioning
confidence: 99%
“…The well-funded medical project related to HIV prevention and care (8) and the longstanding nursing leadership programs (9) concentrated mostly on leadership along with active learning projects. The LI is the first project to our knowledge focusing on rehabilitation leaders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the strategy of nurses initiating ART rather than doctors has a positive impact on increasing ART uptake, although there are still challenges in NIMART training and implementation which affect the performance of HIV programmes as indicated in Table 5. NIMART training can have both positive and negative impacts depending on the strategies used during training [7,8,9,10]. Studies have revealed that nurses feel that NIMART training has empowered them with knowledge and skills to manage PLWH, however, there are still factors that influence [11,12,13,14,15,16].…”
Section: The Impact Of Nimart/hiv Training Strategies On the Implemenmentioning
confidence: 99%
“…[ 44 45 ] Similarly, the Afya Bora (Swahili for “Better Health”) Consortium, formed in response to the need for qualified health care leaders, consists of five Africa-US partnerships in Botswana, Kenya, Uganda, Tanzania, and Cameroon. [ 46 ] The consortium works to develop a powerful collaboration by merging and consolidating education, training, and research experiences and resources. A focused mission prepares future global leaders for careers in health care settings to leverage governmental and nongovernmental organizations (NGOs) to transform health care delivery systems to better serve the citizens of LMICs.…”
Section: Low-and-middle-income Country Perspectivementioning
confidence: 99%
“…A focused mission prepares future global leaders for careers in health care settings to leverage governmental and nongovernmental organizations (NGOs) to transform health care delivery systems to better serve the citizens of LMICs. [ 46 ]…”
Section: Low-and-middle-income Country Perspectivementioning
confidence: 99%